Context-aware systems and applications : 4th International Conference, ICCASA 2015, Vung Tau, Vietnam, November 26-27 2015, revised selected papers /: 4th International Conference, ICCASA 2015, Vung Tau, Vietnam, November 26-27 2015, revised selected papers. (2016) - Unknown
No abstract available